PENGARUH PENJUALAN ONLINE DAN OFFLINE TERHADAP TINGKAT PENJUALAN DALAM PERSPEKTIF ETIKA BISNIS: (Studi Kasus Toko Nana Shop Sedati, Sidoarjo) - Dara Nursyifa Sofian; Amin Sadiqin (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2023)
This study aims to check (1). The impact of online sales on sales levels at Nana Shop Sedati, Sidoarjo. (2). To determine the impact of offline sales on sales levels at Nana Shop Sedati, Sidoarjo. (3) To determine the impact of online and offline sales on sales levels at Nana Shop Sedati, Sidoarjo. This research uses quantitative methods. The type of data is primary and secondary data. Primary data obtained from the results of documentation in the form of Nana Shop sales reports as well as observations and interviews with Nana Shop owners. Based on the results of research at the significance level of 0.05 or 5%, it shows that online and offline sales simultaneously have a significant effect on the level of sales, this is evidenced by the value of F_{count} greater than F_{tabel} (482.910> 4.26. Researchers give advice to Nana Shop owners to improve uploading product photos on online sales and also improve facilities in the store as well as improve the system in implementing online and offline sales.